WhatsApp Group for Teaching and Learning in Indonesian Higher Education: What’s Up? - Rahmadi, Imam Fitri (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Technology plays a pivotal role in today’s teaching and learning process in terms of facilitating learning and improving students’ performance. Exploring an avant-garde technology to be integrated into the classroom is critical for finding new ways of learning. This study aimed at investigating university students’ usage, perception, attitude, and readiness towards the WhatsApp group as a teaching and learning platform. This is an exploratory study engaged in one class of university students after joining a course conducting by integrating a WhatsApp group for teaching and learning platform. The result revealed that students actively use WhatsApp in daily life, but unfortunately passively use it for learning in a group. Students recognise that the WhatsApp group is of potential for ubiquitous learning, and they have a good attitude to this app as a teaching and learning platform. However, it found that students are not ready yet to learn actively, collaboratively, and independently through the WhatsApp group. The academic and practical implications of these findings are discussed, and avenues for future research outlined.